Variation in Tree Species Richness along an Elevation Gradient in the Modi River Basin, Annapurna Conservation Area, Nepal - Khanal, Ram Prasad; Devkota, Shiva; Devkota, Mohan Prasad (Journal of Plant Resources, 2022)
In this study, we studied the pattern and relationship between tree species richness along an elevation gradient in the southern aspect of Modi River Basin, Annapurna Conservation Area (ACA), Central Nepal. Altogether, 30 quadrats were established at 15 elevation bands between 1000 m and 3800 m above the mean sea level. Thirty tree species belonging to 21 families were recorded; Fabaceae had the highest number of species (4 spp.) followed by Betulaceae (3 spp.) and Anacardiaceae (3 spp.). Canonical correspondence analysis (CCA) tool was applied which revealed that the species richness and distribution varied significantly along an elevation gradient. The bimodal pattern of species richness was observed. It is concluded that the higher the elevation level, the lesser the number of tree species, thus, the trees in study site eschewed higher elevation levels.